Relasi Kuasa Antara Pimpinan Dan Barista Chord Café Tidar Kabupaten Jember - Febriyan Dwi Rachman; Hilda Lolita; Rizaldy Andy Wijaya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Cafes or also known as coffee places among today's society, especially teenagers. Cafes are used as a place to hang out and become a business to meet the needs of consumers. In this era of development, many cafes are competing to provide a comfortable place and atmosphere to attract customers, making it suitable as a place to relax, chat or gather. One example is Chord Cafe, this cafe is very strategically located so it is easy to reach and has a comfortable place. Chord Cafe also has many choices of coffee and non-coffee menus as well as snacks and heavy meals. This cafe has baristas who are very skilled in making various kinds of coffee and other drinks. As a fairly large cafe, Cord Cafe often holds live music, this is one way to attract customers to come to the café.